Tert-butylhydroquinone attenuates doxorubicin-induced dysregulation of testicular cytoprotective and steroidogenic genes, and improves spermatogenesis in rats - Godwin Adakole Ujah (Nature Portfolio, 2021)
Abstract Doxorubicin (DOX) is a broad-spectrum chemotherapeutic drug used in the treatment of cancers. It acts by generating reactive oxygen species in target cells. The actions are, however, not limited to cancerous cells as it attacks healthy cells, killing them. This study investigated the benefits of the antioxidant, tert-butylhydroquinone (tBHQ), on testicular toxicity following DOX therapy. Twenty-four adult male albino rats were assigned randomly into four groups (n = 6), namely: normal control (NC), tBHQ, DOX and tBHQ + DOX groups. tBHQ (50 mg/kg body weight in 1% DMSO) was administered orally for 14 consecutive days, while a single DOX dose (7 mg/kg body weight) was administered intraperitoneally on Day 8. DOX decreased sperm count, motility and viability, and decreased the levels of steroidogenesis-related proteins, and reproductive hormones. Furthermore, DOX decreased the expression of antioxidant cytoprotective genes, and decreased the protein level of proliferating cell nuclear antigen in the testis. Conversely, DOX increased the expression of pro-inflammatory and pro-apoptotic genes in the testis. These negative effects were ameliorated following the intervention with tBHQ. Our results suggest that tBHQ protects the testis and preserves both steroidogenesis and spermatogenesis in DOX-treated rats through the suppression of oxidative stress, inflammation and apoptosis.